Ethylenediaminetetraacetic acid (EDTA) as an auxiliary tool in the electrospray ionization mass spectrometry analysis of native and derivatized β-cyclodextrins, maltoses, and fructans contaminated with Ca and/or Mg - Giudicessi, S.L. (2010)
The effect of Ca2+ (and Mg2+) and the disodium salt of ethylenediaminetetraacetic acid (EDTA), a well known Ca2+ (and Mg2+) chelating agent, on the volatilization/ionization of carbohydrates by using electrospray ionization mass spectrometry has been studied. Model compounds such as maltoses (maltose to maltoheptaose), β-cyclodextrins (β-cyclodextrin, methyl-β-cyclodextrin, heptakis(2,6-di-O-methyl)-β-cyclodextrin, heptakis(2,3,6-tri-O-methyl)-β-cyclodextrin, and 2-hydroxypropyl-β-cyclodextrin) and fructans (sucrose, 1-ketose, nystose, and 1F-fructofuranosylnystose) were used. © 2010.